2005
DOI: 10.1002/jts.20076
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of posttraumatic stress among Western New York undergraduates following the September 11th terrorist attack on the World Trade Center

Abstract: The structure of posttraumatic stress is of both theoretical and clinical interest. In the present study, seven models of posttraumatic stress were compared using confirmatory factor analysis. A sample of 528 Western New York undergraduate students was assessed 1 and 3 months after the September 11th, 2001 terrorist attacks. At the Month 1 assessment, the current three-factor Diagnostic and Statistical Manual of Mental Disorders (DSM-IV; American Psychiatric Association, 1994) model, which consists of Intrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
94
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 26 publications
18
94
1
1
Order By: Relevance
“…A fourfactor, intercorrelated model, with factors described as intrusions, avoidance, dysphoria, and hyperarousal, provided the best overall fit. More recent studies have also supported this solution (Baschnagel et al, 2005;Palmieri, Weathers, et al, 2007). Additionally, Asmundson et al (2000) compared the fit of five symptom models, including Taylor et al's two-factor model (1998), two four-factor models examined by King et al (1998), and two three-factor models based on DSM-IV criteria, in a group of primary care patients.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…A fourfactor, intercorrelated model, with factors described as intrusions, avoidance, dysphoria, and hyperarousal, provided the best overall fit. More recent studies have also supported this solution (Baschnagel et al, 2005;Palmieri, Weathers, et al, 2007). Additionally, Asmundson et al (2000) compared the fit of five symptom models, including Taylor et al's two-factor model (1998), two four-factor models examined by King et al (1998), and two three-factor models based on DSM-IV criteria, in a group of primary care patients.…”
mentioning
confidence: 74%
“…To date, exploratory factor analyses of DSM-III-R/DSM-IV PTSD symptoms have been conducted with numerous populations, including survivors of fires, motor vehicle accidents and assaults, United Nations peacekeepers, refugees, and military veterans (Fawzi et al, 1997;Foa, Riggs, & Gershuny, 1995;Keane, 1993;Maes et al, 1998aMaes et al, , 1998bSack, Seeley, & Clarke, 1997;Shelby, Golden-Kreutz, & Andersen, 2005;Smith, Redd, DuHamel, Vickberg, & Ricketts, 1999;Smith, Perrin, Dyregrov, & Yule, 2003;Stewart et al, 1999;Taylor, Kuch, Koch, Crockett, & Passey, 1998). Two-, three-, four-, and five-factor solutions have been reported, with no solution clearly paralleling the symptom clusters suggested by the most recent versions of the DSM.Along with these exploratory factor analyses, numerous confirmatory factor analyses (CFAs) of DSM-III-R/DSM-IV PTSD symptoms have been conducted (Andrews, Joseph, Shevlin, & Troop, 2006;Anthony, Lonigan, & Hecht, 1999;Anthony et al, 2005;Asmundson et al, 2000;Asmundson, Wright, McCreary, & Pedlar, 2003;Baschnagel, O'Connor, Colder, & Hawk, 2005;Buckley, Blanchard, & Hickling, 1998;Cordova, Studts, Hann, Jacobsen, & Andrykowski, 2000;DuHamel et al, 2004;King, Leskin, King, & Weathers, 1998;Maes et al, 1998aMaes et al, , 1998bMarshall, 2004;McWilliams, Cox, & Asmundson, 2005;Palmieri & Fitzgerald, 2005; Palmieri, Marshall, & Schell, 2007; Palmieri, Weathers, Difede, & King, 2007;Sack et al, 1997;Simms, Watson, & Doebbeling, 2002;Stewart et al, 2004). CFAs have several advantages over exploratory factor analyses in elucidating the structure of PTSD symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presentation of these nonspecific symptoms might be related to other hyperarousal symptoms for individuals with PTSD, but more related to the experience of emotional numbing and anhedonia for those primarily experiencing depression. This might explain why studies to date employing samples with a high rate of PTSD support the King model (e.g., Palmieri&Fitzgerald, 2005), whereas the Simms dysphoria model has been supported in studies utilizing nonclinical samples (Baschnagel et al, 2005;Messer et al, 2007;Simms et al, 2002). A multigroup study that examines the factor structure of PTSD symptoms across clinical groups would be useful in testing this conjecture.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed by King and colleagues (2006), many studies employing a variety of symptom questionnaires and populations support a 4-factor model (King, Leskin, King, & Weathers, 1998) that includes reexperiencing, avoidance, numbing, and hyperarousal factors (Andrews, Joseph, Shevlin, & Troop, 2006;Asmundson et al, 2000;Marshall, 2004;Palmieri & Fitzgerald, 2005). The reexperiencing and hyperarousal factors are analogous to DSM-IV symptom Clusters B and D, and the numbing and avoidance factors are drawn from Cluster C. In contrast, other studies have supported a 4-factor model identified by Simms and colleagues (2002), that includes intrusions, avoidance, dysphoria, and hyperarousal (Baschnagel, O'Connor, Colder, & Hawk, 2005;Messer, Hoge, & Castro, 2007). Here, intrusion and avoidance factors correspond to King et al's (1998) reexperiencing and avoidance factors.…”
mentioning
confidence: 95%